Qualitative and Quantitative Analysis of Cardiac Progenitor Cells in Cases of Myocarditis and Cardiomyopathy - Gerisch, Marie; Smettan, Jan; Ebert, Sabine; Athelogou, Maria; Brand-Saberi, Beate; Spindler, Nick; Mueller, Wolf C.; Giri, Shibashish; Bader, Augustinus (Frontiers in Genetics, 2018)
We aimed to identify and quantify CD117+ and CD90+ endogenous cardiac progenitor cells in human healthy and diseased hearts. We hypothesize that these cells perform a locally acting, contributing function in overcoming medical conditions of the heart by endogenous means. Human myocardium biopsies were obtained from 23 patients with the following diagnoses: Dilatative cardiomyopathy (DCM), ischemic cardiomyopathy (ICM), myocarditis and controls from healthy cardiac patients. High-resolution scanning microscopy of the whole slide enabled a computer-based immunohistochemical quantification of CD117 and CD90. Those signals were evaluated by Definiens Tissue Phenomics® Technology. Co-localization of CD117 and CD90 was determined by analyzing comparable serial sections. CD117+/CD90+ cardiac cells were detected in all biopsies. The highest expression of CD90 was revealed in the myocarditis group. CD117 was significantly higher in all patient groups, compared to healthy specimens (*p < 0.05). The highest co-expression was found in the myocarditis group (6.75 ± 3.25 CD90+CD117+ cells/mm²) followed by ICM (4 ± 1.89 cells/mm²), DCM (1.67 ± 0.58 cells/mm²) and healthy specimens (1 ± 0.43 cells/mm²). We conclude that the human heart comprises a fraction of local CD117+ and CD90+ cells. We hypothesize that these cells are part of local endogenous progenitor cells due to the coexpression of CD90 and CD117. With novel digital image analysis technologies, a quantification of the CD117 and CD90 signals is available. Our experiments reveal an increase of CD117 and CD90 in patients with myocarditis.